Factors Associated With Malaria Prevalence among Children Aged Below Five Years in North West Kisumu Ward, Kisumu County - Midem, Otieno David (JOOUST, 2021)
Malaria is a major public health problem globally. In 2019, about 229 million cases were reported globally. The WHO African region accounted for approximately 94% of total malaria cases and about 51% of total malaria deaths. In areas of high malaria transmission, children under the age of 5 years are particularly susceptible to illness and death. In Kenya, malaria is the leading cause of morbidity and mortality among children under the age of 5 years. Despite heightened malaria prevention and control measures such as distribution of long lasting insecticide treated nets, chemotherapy and health education, North West Kisumu ward still has a high malaria burden, with 40% of total malaria cases occurring among children under the age of five years. This cross-sectional study was conducted at Chulaimbo County Hospital to investigate the factors associated with the high malaria prevalence among children under the age of five years in North West Kisumu ward, using randomly selected 369 children (both malaria positive and negative). Data was collected from the respondents by use of a questionnaire, and entered into Microsoft Excel, and analyzed by SPSS version 20. Chi square test of independence was used to determine the relationship between socio-economic, demographic factors and malaria prevalence, as well as the association between mosquito bed net usage characteristics, child nutritional status and malaria prevalence. Child age was significantly associated with malaria (p=0.04). There were low malaria odds among females (OR, 0.92; 95% CI, 0.61-1.39) and in households where mothers (OR, 0.47; 95% CI, 0.16-1.37) or fathers (OR, 0.86; 95% CI, 0.31-2.35) had university education. Low malaria odds was also reported among children whose fathers had employment (OR, 0.94; 95% CI, 0.49-1.80). On the contrary, high malaria risk was recorded among children whose mothers had employment (OR, 1.24; 95% CI, 0.62-2.50). Children from married respondents were likely to test positive for malaria (OR, 1.07; 95% CI, 0.60- 1.93). Children who had bed nets were less likely to test positive for malaria (OR, 0.70; 95% CI, 0.35-1.41). Surprisingly, this study reported low malaria risk among severely malnourished children (OR, 0.71; 95% CI, 0.42-1.20). Child age and bed net use, but not nutritional status, are therefore important determinants of malaria prevalence in children under 5 years. The Ministry of Health should promote more efforts towards protecting young children from malaria, by ensuring access and use of bed nets, and enhancing health education.